The Redox Chemistry of Ruthenium Dioxide: A Cyclic Voltammetry Study—Review and Revision - Sebastian Chalupczok; Peter Kurzweil; Helmut Hartmann; Christian Schell (International Journal of Electrochemistry)
By cyclic voltammetry at high scan rates, the electrochemical properties of RuO2 in acidic and alkaline solutions were investigated in detail. Thirteen current peaks can be distinguished in sulfuric acid and sodium hydroxide. With respect to the pH sensitivity of RuO2 electrodes, we considered charge calculations, peak currents, and apparent diffusion coefficients. The nature of the Ru(II) oxidation was clarified by Ru(I)−Ru(III) species.